“The contemporaries’ opinions of him are so varied...”: The personality of Vasyl’ Karazin (1773–1842) as seen by the people who knew him - Vovk, Olga I.; Вовк, Ольга Ігорівна (Praha : Evropský filozofický a historický diskurz, 2020)
In the present paper, the contemporaries’ impressions about the personality of a famous scientist and public figure Vasyl’ Nazarovych Karazin (1773–1842) were researched. For this purpose, the massif of ego‐documents (diaries, letters, memoirs) was analyzed. These sources were created by people from different communication “circles” of V. N. Karazin (the family, Kharkiv and Ukrainian‐Sloboda community, contacts in the Moscow and Saint‐ Petersburg) except for his foreign acquaintances and correspondents. Processes of origin, forming and fixing of V. N. Karazin’s images in each defined social groups were described. Also, objective and subjective factors that influenced these processes were discovered. Directions for further research related to the study of the impact of opinions about V. N. Karazin’s personality during his lifetime for the further formation of his historiographical images were defined.